Endometriosis ¿por qué reproducción asistida? - Vergara Herrera, Carlos Alfredo (2026)
Endometriosis is a chronic, estrogen-dependent gynecological disease that affects approximately 10% of women of reproductive age and is associated with infertility in up to 50% of cases[1]. The link between endometriosis and infertility is explained by anatomical distortion, peritoneal inflammation, decreased ovarian reserve, andimpaired endometrial receptivity[2]. Traditionally, laparoscopic surgery has been used as a first-line approach to restore pelvic anatomy; however, its benefits in terms of live birth rates are limited and it carries the risk of reducing ovarian reserve.[3] In contrast, in vitro fertilization (IVF) has demonstrated higher cumulative pregnancyrates in a shorter time, bypassing the anatomical and pathophysiological barriers of the disease[4]. International societies such as ESHRE currently discourage routinesurgery before IVF and recommend prioritizing assisted reproduction, reserving surgical intervention for selected cases: severe pelvic pain, large endometriomas (>4 cm) preventing access to follicles during oocyte retrieval[5], or those suspicious formalignancy, given the 1–1.5% increased risk of ovarian cancer in these patients[6, 7, 8]. Surgery is also indicated in cases of hydrosalpinx or organ involvement.[5]. This review summarizes the most recent evidence and argues why assisted reproduction should be considered the central strategy in managing endometriosis-associated infertility.